Trade reforms and current account imbalances - Jiangdong Ju; Kang Shi; Shang-Jin Wei (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
In partial equilibrium, a reduction in import barriers may be thought to lead to an increase in imports and a reduction in trade surplus. However, the general equilibrium effect can go in the opposite direction. We study how trade reforms affect current accounts by embedding a modified Heckscher-Ohlin structure and an endogenous discount factor into an intertemporal model of current account. We show that trade liberalizations in a developing country would generally lead to capital outflow. In contrast, trade liberalizations in a developed country would result in capital inflow. Thus, efficient trade reforms can contribute to global current account imbalances, but these imbalances do not need policy "corrections".
URN:NBN:fi:bof-201408072212
Keywords: F3; F4; 330